Relationship between nursing care quality, nurse staffing, nurse job satisfaction, nurse practice environment, and burnout: literature review - Koy, Virya; Yunibhand, Jintana; Angsuroch, Yupin; Fisher, Mary L. (International Journal of Research in Medical Sciences, 2017)
The purpose of this literature review is to explore the relationship between nurse staffing, nurse job satisfaction, nurse practice environment, burnout, and nursing care quality through a consideration of what is meant by perceptions of nursing care quality. Different people define nursing care quality in many ways. It is complex, multi-faceted and multi-dimensional, and attempts to assess, monitor, evaluate and improve nursing care quality have evolved over a number of years. Of particular interest is the way in which changes in nurse staffing, nurse job satisfaction, nurse practice environment, and burnout may affect the quality of nursing care delivery. A search was conducted using the CINAHL, Medline and Embase databases, HINARI, Science Direct, Google, and PubMed. The terms searched included quality of health care; nursing care quality; nurse job satisfaction; nurse practice environment; burnout; and nurse staffing. Papers were included for their relevance to the field of enquiry. The original search was conducted in 2003 and updated in 2004. Quality of care is a complex, multi-dimensional concept, which presents researchers with a challenge when attempting to evaluate it. Many different tools have assessed nursing care quality. In addition, the review found that there were relationships between nurse staffing, nurse job satisfaction, nurse practice environment, burnout, and nursing care quality.